Systemic gene dysregulation in classical Galactosaemia: Is there a central mechanism? - TREACY, EILEEN (My University, 2014)
Classical Galactosaemia is a rare disorder of carbohydrate metabolism caused by a deficiency of galactose-1-phosphate uridyltransferase (GALT). The disease is life-threatening in the neonate, and the only treatment option is life-long dietary restriction of galactose. However, long-term complications persist in treated patients including cognitive impairments, speech and language abnormalities and premature ovarian insufficiency in females. Microarray analysis of T-lymphocytes from treated adult patients identified systemic dysregulation of numerous gene pathways, including the glycosylation, inflammatory and inositol pathways. Analysis of gene expression in patient-derived dermal fibroblasts of patients exposed to toxic levels of galactose, with immunostaining, has further identified the susceptibility of the glycosylation gene alpha-1,2-mannosyltransferase (ALG9) and the inflammatory gene annexin A1 (ANXA1) to increased galactose concentrations. These data suggest that Galactosaemia is a multi-system disorder affecting numerous signalling pathways.
PUBLISHED
Keywords: Galactosaemia; Biomarkers; Genomics; Glycosylation; Inflammation